Subtract and simp \( 6 \frac{3}{10}-2 \frac{2}{5} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
First, let’s convert the mixed numbers into improper fractions. For \( 6 \frac{3}{10} \), we have \( 6 \times 10 + 3 = 60 + 3 = 63 \), so it becomes \( \frac{63}{10} \). For \( 2 \frac{2}{5} \), we have \( 2 \times 5 + 2 = 10 + 2 = 12 \), which makes it \( \frac{12}{5} \). Next, we need a common denominator to subtract these fractions. The least common multiple of 10 and 5 is 10. Thus, we convert \( \frac{12}{5} \) into \( \frac{24}{10} \). Now, we can subtract: \[ \frac{63}{10} - \frac{24}{10} = \frac{63 - 24}{10} = \frac{39}{10} \] To simplify, we can convert back to a mixed number: \[ \frac{39}{10} = 3 \frac{9}{10} \] So, \( 6 \frac{3}{10} - 2 \frac{2}{5} = 3 \frac{9}{10} \).